Women artists the twentieth century. - Petersen, Karen, 1943-; Wilson, J. J., 1936-; Harper & Row, Publishers (Harper & Row, Publishers, 1975)
Presents views of paintings and sculpture by European and American women of the twentieth century.
Authors, Karen Petersen, J. J. Wilson.
Keywords: Art, Modern -- 20th century; Women artists